Home language environment of Polish children in Iceland and their achievement in Icelandic grammar school - Anna Wozniczka (2011)
Nobody doubts the importance of the mother tongue in raising bilingual children, but the possible influences of growing up in two or more languages on the child’s development are the subject of rich discussion. How does the quality of mother language input, including reading and other child-parent language interactions, affect the child’s development and achievement in school? Examining this question is particularly interesting in Iceland, a country which in recent decades changed from a rather homogenous to a multicultural one and where number of foreign citizens (most of them of Polish origin) oscillates around 8%. Although there has been research on acquisition of the second language of immigrant children in Iceland, as well as on mother tongue teaching and L1 and L2 acquisition in other Nordic countries, there is a need for deeper research of the various language environments of a particular immigrant group and the possible influences of these environments. This study is based both on qualitative and quantitative inquiry. The field work consisted of semi-structured interviews with fifteen children of the Polish speaking community in Iceland, selected based on characteristics such as gender, socio-cultural background and future plans of the family. Moreover, parents of interviewed children received a questionnaire on frequency of child-parent activities related to language development and school achievement. Later, children’s grades in Icelandic were collected. Data were systematised, interrelated and interpreted. This study tried to assess the language environment of Polish immigrant children to help explain their achievements in school. Results indicated that Polish played a much more important role in parent-child home language interactions. However, it seemed that parents’ attitude towards Icelandic did not deter their children from achieving good results in that language, because parents, concentrating on interactions in the Polish language, were unintentionally helping their children to develop language ...